A modalização em e-mails pruduzidos em ambiente organizacional: uma abordagem na perspectiva do interacionismo sociodiscursivo - KLAUTAU, Eneida Lúcia Garcia (Universidade Federal do Pará, 2012)
This study is situated in the field of research on the role of language in workplace activities. It is based on the theoretical and methodological assumptions of sociodiscursive interactionism (BRONCKART, 2009), which is dedicated, in special, to the analysis of textual materiality and, consequently, to the activity of textualization. Based on the assumption that every empirical text brings marks of the representations of the verbal agents in relation to the particular active situation in which they are situated (BRONCKART, 2009), we have established, as the general aim of this study, to investigate, in the materiality of the written text, the modal linguistic units as a sign of the representations of the enunciator in the parameters of his or her situation of interlocution. In particular, the goal we set was, through a descending method analysis, to investigate, in the text genre of workplace e-mails, whether or not modalization occurs, and which types – logical, deontic, appreciative or pragmatic – are most utilized by the enunciator. We attempt to infer why they occur (or still, do not occur) as well as their type, based on possible representations of the agent-producer in relation to the relative interlocution parameters, e.g. the social role which him or herself play in the interlocutory act; the social role of its addressee; the social place which both occupy in the work environment and the thematic content linked to the text. Our hypothesis here is that modalization, related as it is to these representations of the enunciator, is more present in textual productions which go from the bottom up in the company‟s hierarchical structure (that is, from subaltern to managership). It is less present, or sometimes even inexistent, in textual productions which go from top to bottom (that is, from managership to subaltern).